Anatomical Reconstruction in Bilateral Cleft Lip With Mendoza Technique. Issue 6 (September 2018) - Pérez González, Araceli; Arámburo-García, Rigoberto
Abstract : N/A: The bilateral cleft lip (BCL) is the most severe manifestation of orofacial clefts. Multiple techniques have been described to reconstruct BCL to obtain good aesthetic and functional results with minimal complications. Objective: Description of surgical technique for BCL reconstruction and present the postoperative results obtained. Methods: Patients with BCL of the cleft lip and palate at ABC Medical Center from June 2013 to June 2017 operated with Mendoza bilateral cheiloplasty were included. The procedure includes an anatomical reconstruction of the lip with minimal resection of tissue, alignment of the orbicularis muscle, vestibule creation, and complete use of the prolabium. The evaluation was carried out by photographs analyzing parameters of quality, symmetry, and alignment of lip and nose structures. Results: The authors included 36 patients, 15 women and 16 men. The average procedure time was 57 minutes. Photographs were evaluated 1 year postoperatively, symmetry in lip was observed in 91.6% of the patients, muscle continuity in 100%, deep gingivolabial sulcus in 94.5% of cases, closed nasal floor in 100% with no presence of nasovestibular fistulas. Conclusions: This technique allows an anatomical BCL reconstruction with good aesthetic and functional results.